Design and Development of an Online Analytical Processing (OLAP) Application for Customer Profiling Analysis of Insurance "X" - Kesuma Wardanie, Debleng Puja; Kacung, Slamet; Fauzi, Chamdan; Pamudi, Pamudi (Knowbase : International Journal of Knowledge in Database, 2024)
The system's slow and inflexible response time is a characteristic of analytical processes based on transactional databases (OLTP), as experienced by PT Asuransi "X." This limitation arises because transactional databases are not designed for OLAP, which can provide various functions to perform synthesis and analysis that improve response time. This study aims to design and develop an Online Analytical Processing (OLAP) application to be used for customer profiling analysis at insurance company "X." In the insurance industry, effective and efficient data analysis is essential to understand customer behavior, perform segmentation, and make more informed decisions in marketing insurance products. The OLAP application developed in this study integrates various customer data dimensions, such as demographics, claim history, and owned products, facilitating multidimensional analysis for its users. The application design process includes system design, data collection, OLAP technology implementation, and application testing. The study results indicate that the application reveals that the majority of customers are male (56%), aged between 30 and 45 years (45%), and employed in the private sector. Additionally, in the city of Surabaya, there is a higher tendency to purchase the Mitra Sakinah life insurance policy. This information enables the company to better understand customer demographic characteristics and tailor its marketing strategies accordingly.